ANALISIS KEPUTUSAN PEMBELIAN PRODUK â€œLELONGâ€ PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS TANJUNGPURA - Nurhanida, Nurhanida; Witarsa, Witarsa; Budiman, Jumardi; Okianna, Okianna; Kuswanti, Heni (STKIP Persada Khatulistiwa Sintang, 2023)
One of the products that students are interested in today is the products of imported used goods that are often referred to as